Comparative performance of airyscan and structured illumination superresolution microscopy in the study of the surface texture and 3D shape of pollen. Issue 2 (1st August 2016) - Sivaguru, Mayandi; Urban, Michael A.; Fried, Glenn; Wesseln, Cassandra J.; Mander, Luke; Punyasena, Surangi W.
Abstract: The visualization of taxonomically diagnostic features of individual pollen grains can be a challenge for many ecologically and phylogenetically important pollen types. The resolution of traditional optical microscopy is limited by the diffraction of light (250 nm), while high resolution tools such as electron microscopy are limited by laborious preparation and imaging workflows. Airyscan confocal superresolution and structured illumination superresolution (SR‐SIM) microscopy are powerful new tools for the study of nanoscale pollen morphology and three‐dimensional structure that can overcome these basic limitations. This study demonstrates their utility in capturing morphological details below the diffraction limit of light. Using three distinct pollen morphotypes ( Croton hirtus, Dactylis glomerata, and Helianthus sp.) and contrast‐enhancing fluorescent staining, we were able to assess the effectiveness of the Airyscan and SR‐SIM. We further demonstrate that these new superresolution methods can be easily applied to the study of fossil pollen material.